1992
DOI: 10.1042/bj2860637
|View full text |Cite
|
Sign up to set email alerts
|

Malonyl-CoA inhibition of peroxisomal carnitine octanoyltransferase

Abstract: Although the malonyl-CoA sensitivity of peroxisomal carnitine octanoyltransferase (COT) is reportedly lost on solubilization, we show that malonyl-CoA does inhibit the purified enzyme. Assay conditions such as buffer composition, pH, acyl-CoA substrate and the presence or absence of BSA can affect the observed inhibition. When assayed in the absence of BSA, COT shows simple competitive inhibition by malonyl-CoA. The Ki value for inhibition of purified COT is high (106 microM) compared with physiological concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…As mentioned before, CPT1A is the rate-limiting and most highly regulated step in ␤-oxidation. Interestingly, the dominant allosteric inhibitor malonyl-CoA regulates CROT similarly to CPT1A (28,52). In an elegant twist, evolution has maintained the regulation by miR-33 of two enzymes that are sensitive to malonyl-CoA by miR-33.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned before, CPT1A is the rate-limiting and most highly regulated step in ␤-oxidation. Interestingly, the dominant allosteric inhibitor malonyl-CoA regulates CROT similarly to CPT1A (28,52). In an elegant twist, evolution has maintained the regulation by miR-33 of two enzymes that are sensitive to malonyl-CoA by miR-33.…”
Section: Discussionmentioning
confidence: 99%
“…They are all immunologically distinct [16][17][18][19], and sequencing of the cDNA of several of them has so far indicated that they are separate gene products [20][21][22][23]. Interestingly, the pattern that appears to be emerging from ongoing studies is that each of these membrane systems possess two isoforms of CPT, the activity of only one of which is sensitive to malonyl-CoA inhibition [23][24][25][26][27][28][29].…”
Section: Enzymes Involved In the Partitioning Of Fatty Acids Between mentioning
confidence: 99%
“…Mutations H131A and H340A in peroxisomal COT did not have an important effect on the kinetic behaviour of the mutants with carnitine, as the differences in K m values observed for carnitine are small in either purified or peroxisomal COTs [14]. This was expected, as previous results showed that a different residue (Arg-505) of the bovine COT had a role in binding to carnitine [40].…”
Section: Discussionmentioning
confidence: 51%
“…Studies by A'Bhaird and Ramsay [14] show that malonyl-CoA binds to rat peroxisomal COT at two separate sites. At one of these sites, which is within the catalytic domain, malonyl-CoA competes with the substrate, either palmitoyl-CoA or decanoylCoA, in a similar way to the inhibition produced by several CoA esters, like glutaryl-CoA, 3-hydroxy-3-methylglutaryl-CoA and methylmalonyl-CoA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation